Highly thermostable RhB@Zr-Eddc for the selective sensing of nitrofurazone and efficient white light emitting diode - Shen, Yanqiong; Ma, Di; Zhao, Mian; Qian, Jinjie; Li, Qipeng (Frontiers in Chemistry, 2024)
Highly thermostable RhB@Zr-Eddc composites with the Rhodamine B (RhB) enclosed into the nanocages of Zr-Eddc was synthesized by one-pot method under hydrothermal conditions, whose structure, morphology and stability were characterized through the X-ray powder diffractometry (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). RhB@Zr-Eddc showed the highly thermal stability up to 550 ℃ and emitted the bright red-light emission at 605 nm, which could highly selective detect the nitrofurazone (NFZ) among eleven other antibiotics in aqueous solution. Furthermore, via combining the RhB@Zr-Eddc with commercial green phosphor (Y3Al5O12:Ce 3+ , Ga 3+ ), the mixture was encapsulated onto a 455 nm blue LED chip, creating an excellent white light-emitting diode (WLED) device with the correlated colour temperature (CCT) of 4710 K, luminous efficiency (LE) of 43.17 lm/w and colour render index (CRI) of 89.2.